Waste management due to the phenomenon of overtourism at the tourist destination "Ngambang Tirto kencono" Ponorogo - Adam Hilman, Yusuf; Khoirurrosyidin, Khoirurrosyidin; Azhar, Insyira Yusdiawan; Putri, Seventeena Agustin Veby Kartika (Kontribusia : Research Dissemination for Community Development, 2025)
The problem we face is the accumulation of waste when tourist visits increase. Until now, there has been no effective way to address this issue, so we took the initiative to manage waste using the 5R concept: reduce, repair, reuse, recover, and recycle. We utilise a plastic waste recycling method to create useful items. The process is carried out in three stages: 1) Conducting a workshop, 2) Producing recycled waste, and 3) Distributing the useful items created during the workshop. Following these activities, the community has gained a better understanding of the importance of utilising waste to create useful items, thereby helping to reduce plastic waste around tourist destinations. We recommend organising a waste festival to enhance the popularity of tourist attractions and raise awareness about waste management.